Unique Sensitivity of Uterine Tissue and the Immune System for Endometriotic Lesion Formation - Morris, Stephanie A.; Korach, Kenneth S.; Burns, Katherine A. (Frontiers in Physiology, 2021)
Endometriosis is a debilitating disease that affects about 10% of reproductive-aged adolescents and women. The etiology of the disease is unknown; however, a prevailing hypothesis is that endometriosis develops from retrograde menstruation, where endometrial tissue and fluids flow back through the oviducts into the peritoneal cavity. There is no cure for endometriosis, and symptoms are treated palliatively. Despite the advances in knowledge, the complexity of endometriosis etiology is still unknown. Recent work by our group suggests that the initiation of endometriosis is immune-dependent. Using a mouse model of endometriosis, we hypothesized the initiation of endometriosis is immune regulated and uterine endometrium specific. In the absence of a functional immune system non-obese diabetic/severe combined immunodeficiency (NOD/SCID mice), endometriotic lesions did not form. Uterine endometrial tissue forms endometriotic lesions, whereas tissues with differing basal expression levels of estrogen receptor alpha (ESR1) and estrogen receptor beta (ESR2), similar cellular composition to uterus (i.e. bladder, mammary gland, and lung), and treated with estradiol did not form lesions. As MMP7 is known to play a major role in the organization/reorganization of the endometrium during the menstrual cycle, blocking metalloproteinase (MMP) activity significantly decreased the invasive properties of these cells. Together, these findings suggest that endometriosis is immune and uterine specific and that MMP7 likely plays a role in the ability of uterine tissue and the innate immune system to establish and maintain endometriotic lesions.